IMPLEMENTATION OF PRODUCT STANDARDIZATION POLICY SMALL AND MEDIUM INDUSTRY (IKM) IN WOOD PROCESSING RESULTS - Wijaya Wijaya; Sri Mulyani; Emiliana Emiliana (UNTAG Law Review, 2017)
The policy of the Minister of Trade which stipulates Ministerial Regulation No. 97 / M-DAG / PER / 12/2014 on the provisions on the export of forestry industry products implements the obligation to apply product standardization with SVLK (Timber Legality Verification System) to processed wood products from January 1, 2015. SVLK requirements for Small and Medium Enterprises (IKM), especially wood furniture and handicraft industries, are simplified in the form of self declaration as set forth in the document "Export Declaration." However, the Export Declaration Policy set by the government as an alternative for furniture business actors who do not have SVLK does not apply in European market and Australia. The results of research in Central Java Province found the furniture industry as a superior product, the number of SMEs that canceled its export contract causing the loss by stopping furniture exports even though this effort is done by the government in order to improve competitiveness.